Scorpions and Their Human Mortality Report in Iran: A Review Article - Faranak FIROOZFAR; Abedin SAGHAFIPOUR; Nahid JESRI (Tehran University of Medical Sciences, 2019)
Background: The scorpions have enjoyed medical importance from ancient times because of their morphological structure and venom. The identification of the species of these arthropods has been more emphasized than any other aspects. The purpose of this study was to determine scorpion's fauna and mortality rates of their victims as reported in Iran. Methods: In this review, published documents during 1966-2018 related to medically important scorpions and mortality reports due to scorpionism were searched in the data bases such as Web of Science, PubMed, Scopus, Google Scholar and etc., using key words including scorpion, species, classification, Iran, family, species, and the names of all 31 provinces of Iran. Results: Overall, 169 sources were found. Based on the STROBE checklist, the quality of the documents was also considered, and ultimately, 95 sources were selected. Sixty-four species of scorpions have been identified in Iran and 86% of the species belong to the Buthidae family, and the rest (9.5%, 4.5%) belong to the Hemiscorpiidae and Scorpionidae families, respectively. These species live mostly in tropical regions of Iran. The dangerous scorpions and their mortality reports are often recorded from southern regions such as Khuzestan and Hormozgan provinces. Conclusion: Due to the significant increase in the abundance of scorpions in Iran over the past 30 years, it is expected that this trend will continue by researchers, and the fauna of scorpions is regularly reconsidered.